Imaging of the musculoskeletal system - Pope, Thomas Lee (Expert radiology series, 2008)
Helps you to select and interpret imaging studies for the challenges that you face in musculoskeletal diagnosis. This work covers various aspects of musculoskeletal radiology, including diagnostic modalities and interventional techniques.